Carotid intima-media thickness as an indicator of subclinical atherosclerosis in systemic lupus erythematosus patients - Asmaa A Abozeid; Mohammed Hazem; Ali M Altaher; Essam A Abda; Sahar A Elsayed (Wolters Kluwer Medknow Publications, 2021)
Background and aim Accelerated atherosclerosis is a leading cause of increased cardiovascular morbidity and mortality in patients with systemic lupus erythematosus (SLE). Atherosclerosis is mediated by multifactorial processes including inflammation, endothelial dysfunction, autoantibodies, dyslipidemia, and traditional risk factors. So, we aimed to evaluate carotid intima-media thickness (CIMT) for early detection of subclinical atherosclerosis in patients with SLE and to determine its correlation with disease activity. Patients and methods A total of 50 patients with SLE and 50 healthy controls were included in this study. Full detailed history, clinical examination, and laboratory findings for all the participants were recorded. ECG was done for the patients and controls for the detection of QT dispersion. CIMT was measured bilaterally at the distal common carotid artery. Results On measuring CIMT, we found thickened CIMT (>0.8 mm) in 28% and plaques in 18% of the patients. There was a highly significant increase in the right CIMT, left CIMT, and mean CIMT of both sides in the patients in comparison with the controls (P<0.0001, P=0.004, and P<0.0001, respectively). The ECG findings showed that 40% of our patients had normal ECG, 10% had abnormal ST segment, 34% had sinus tachycardia, and 16% had QT dispersion. Moreover, CIMT was positively correlated with SLE disease activity index (SLEDAI) and associated with other nontraditional risk factors including age, disease duration, anti-dsDNA, C3, and nephritis. Conclusion Premature atherosclerosis is a devastating health problem in patients with SLE, which may be accelerated by multiple risk factors related to the disease process and medications; hence, early detection of subclinical atherosclerosis through the measurement of CIMT using carotid ultrasonography is a reliable noninvasive technique to allow early therapeutic intervention and to reduce the mortality.